Riesgos de la salud del docente - Palma Pacheco, Gisela Verónica (2017)
This research has discussed to describe the occupational health risks of teachers, through a bibliographic and field research, that allows identifying occupational diseases, for that reason, it analyzed the health risks in teachers, which it originates in the occupational area, as well as also, it identified the work areas that most affect the health from the institutional environment, this situation contributed to describe different teacher diseases acquired through as professionals in daily life activities. This analysis allowed the prevention and control of occupational health risks in the school using training and preventing techniques which have as their main guideline the development training strategies to help the teachers to identify patterns that involve occupational activities in the future without risk to their health. These actions have to express interests, problems and motivations took out from the educational institution, due to each school can understand the prevention based on the reality. This research was formative which demanded: the integration of learning to do, learning to know and learning to be, that is to say to know, understand and solve problems according to interests of teachers in health risks of teachers. It applied bibliographic and documental research, to consider strategic facing prevention rules; it was necessary advice and training to teachers in the prevention and control of health....